Effectiveness, structure, and content of nurse counseling in gynecologic oncology: a systematic review - Silvia Raphaelis; Andrea Kobleder; Hanna Mayer; Beate Senn (BMC, 2017)
Abstract Background Gynecological pre-cancer and gynecological cancers are considerable diseases in women throughout the world. The disease and treatment lead to numerous biopsychosocial issues. To improve the outcomes of affected women, several counseling interventions have been tested thus far in nursing research. These interventions target different endpoints and are composed of various structural and content components. The purpose of this research was to systematically review the effectiveness of nurse counseling on any patient outcomes tested so far in gynecologic oncology before, during and after treatment and to explore structure and content components. Methods Experimental, quasi-experimental, and pre-experimental studies assessing the effectiveness of nurse counseling in women with gynecological neoplasia were searched for in PubMed®, CINAHL®, PsychINFO®, Cochrane®, and EMBASE®. Reference lists were hand-searched and relevant authors were contacted. Moreover, the evidence level and methodological quality of the included studies were assessed. Afterwards, the effect of nurse counseling on each identified patient outcome was narratively analyzed. To identify the structural and content components of the included interventions, a structured content analysis was performed. Finally, it was determined which components were associated with favorable outcomes within the included studies. Results Seven experimental and three pre-experimental studies, reporting the effects of 11 interventions on a total of 588 participants, were eligible. No study investigated women with pre-cancer. Three studies had a high, five a moderate, and two a low methodological quality. Positive effects were found on quality of life, symptoms, and healthcare utilization. Eight structural components and four content components composed of various sub-components were identified and linked to specific effects. Conclusions The current evidence base is fragmented and inconsistent. More well-designed, large-scale studies including women with pre-cancer are warranted. Most convincing evidence indicates that nurse counseling can improve symptom distress. Components associated with the most trustworthy effects include nurses with an academic education; repeated and individual consultations during and after active treatment; structured, tailored, interdisciplinary orientated, and theoretically based counseling concepts; specific materials; comprehensive symptom management; and utilization of healthcare services. Healthcare providers and researchers can use the findings of this review for the systematic development of nurse counseling in gynecologic oncology.